Towards Adaptive Information Visualization - A Study of Information Visualization Aids and the Role of User Cognitive Style - Steichen, Ben; Fu, Bo (Frontiers in Artificial Intelligence, 2019)
Information Visualization systems have traditionally followed a one-size-fits-all model, whereby the same visualization is shown to each user, without taking into consideration an individual user’s preferences, abilities, or context. By contrast, given the considerable cognitive effort involved in using Information Visualizations, this paper investigates the effect of an individual user’s cognitive style on Information Visualization performance. In addition, this paper studies several interactive “visualization aids” (i.e. interactive overlays that can aid in visualization comprehension), as well as the effect of cognitive style on aid choices and preferences. The results from a user study show that cognitive style plays a significant role when performing tasks with Information Visualizations in general, and that there are clear differences in terms of individual aid choices and preferences. These findings also provide motivation for the development of adaptive and personalized Information Visualization systems that could better assist users according to their individual cognitive style.